Factors associated with spontaneous reporting of adverse drug reactions in Japan. (21st November 2012) - Yamada, Toru; Watanabe, Yuka; Kusama, Makiko; Sugiyama, Yuichi; Ono, Shunsuke
ABSTRACT Purpose Spontaneous reported adverse drug reactions (ADRs) are currently the main source of pharmacovigilance activities in each country. The number of ADRs reported to the authority warns of safety risks to patients, but it also reflects the efficiency and limitations of the reporting system itself. This article explored how the accumulation of safety information, status in foreign countries (e.g., US approval), drug company attributes, and regulatory actions (e.g., early post‐marketing phase vigilance; EPPV) were associated with the numbers of spontaneously reported ADRs in Japan. Methods All serious ADRs for drugs for which the active ingredients or route of administration were approved in Japan from 2000 through 2005 were collected from the national database. The numbers of serious ADRs within the first 2 and 3 years after launch were analyzed using the negative binominal distribution model. Results The launch lag and the presence of drugs with a similar mode of action were negatively associated with the ADR numbers, but the number of study subjects for the new drug application (NDA) showed no clear association. The number of sales representatives and the implementation of EPPV were positively associated with the ADR numbers. Conclusion The accumulation of foreign post‐market evidence seemed to be more important for drug safety in Japan than was the amount of pre‐approval safety data. The positive impacts of sales representatives and EPPV suggested a critical role for drug companies in drug safety and also the importance of considering how best to collect information in local situations with unique regulatory requirements. Copyright © 2012 John Wiley & Sons, Ltd.